Futures for Post-Pandemic Mathematics Teacher Education: Responsiveness and Responsibility in the Face of a Crisis - Atweh, Bill (Archīum Ateneo, 2023)
COVID-19 has caused unprecedented disruption to mathematics teacher education worldwide. This paper is anchored in our learnings from the experiences of teacher educators at four major universities from the Association of Southeast Asian Nations as they dealt with changes in their programs’ delivery triggered by the pandemic, and raises challenges that remain for the futures of post-pandemic mathematics teacher education. Here, we use the two ethical constructs of responsiveness and responsibility to guide actions in response to a crisis, in order to discuss a range of decisions the participants made to respond to the crisis. Behind their initial response to the emergent conditions, the participants were concerned about maintaining the continuity of their students’ education. Further, we identify remaining challenges for mathematics teacher educators to re-imagine their curriculum, teaching, assessment, and equitable access towards a more relevant, productive, and equitable mathematics teacher education. This study adds to the rapidly increasing literature on the effect of the pandemic on mathematics education in the following three ways: (1) here we take a comprehensive view of the disruptions instigated by the pandemic;, (2) we pay special attention to issues of equity; and (3) we address concerns about possible and desirable post-pandemic futures.